Communication Strategy for Counselor Agriculture During the COVID-19 Pandemic: Ensuring Success and Safeguarding Efforts in the Agricultural Sector - Arifin, Zainol; Alfin, Rita; Suyani, Ida Sugeng; Sutoyo, Sutoyo (Kadiri University - Faculty of Agriculture, 2024)
Agricultural extension endeavors in Bocek Village, Karangploso District persist in bolstering agricultural production despite pandemic restrictions. The study scrutinized the communication strategies employed by agricultural extension personnel in disseminating information to farmer groups during the COVID-19 period. The survey methodology, encompassing cell phone interviews and questionnaires, was administered to 30 farmers and extension workers via purposive sampling. Findings indicated that individual face-to-face and cellular telephone-mediated communications were utilized, as group gatherings were curtailed due to restrictions. Alternatives such as farm and home visits were pursued. Farmers continued to adopt recommended technologies and implement provided recommendations, with the performance of agricultural extension falling within a moderate category. Despite challenges, agricultural extension activities persevered amid the pandemic. The messaging conveyed by BPP Karangploso extension workers not only addresses the needs but also employs language that is comprehensible, enabling farmers to readily grasp and respond effectively to the conveyed message.